Real-time PCR assay for detection and differentiation of Coccidioides immitis and Coccidioides posadasii from culture and clinical specimens. - Sudha Chaturvedi; Tanya R Victor; Anuradha Marathe; Ketevan Sidamonidze; Kelly L Crucillo; Vishnu Chaturvedi (PLoS Neglected Tropical Diseases)
Coccidioidomycosis (Valley fever) is a pulmonary and systemic fungal disease with increasing incidence and expanding endemic areas. The differentiation of etiologic agents Coccidioides immitis and C. posadasii remains problematic in the clinical laboratories as conventional PCR and satellite typing schemes are not facile. Therefore, we developed Cy5- and FAM-labeled TaqMan-probes for duplex real-time PCR assay for rapid differentiation of C. immitis and C. posadasii from culture and clinical specimens. The RRA2 gene encoding proline-rich antigen 2, specific for Coccidioides genus, was the source for the first set of primers and probe. Coccidioides immitis contig 2.2 (GenBank: AAEC02000002.1) was used to design the second set of primers and probe. The second primers/probe did not amplify the corresponding C. posadasii DNA, because of an 86-bp deletion in the contig. The assay was highly sensitive with limit of detection of 0.1 pg gDNA/PCR reaction, which was equivalent to approximately ten genome copies of C. immitis or C. posadasii. The assay was highly specific with no cross-reactivity to the wide range of fungal and bacterial pathogens. Retrospective analysis of fungal isolates and primary specimens submitted from 1995 to 2020 confirmed 168 isolates and four primary specimens as C. posadasii and 30 isolates as C. immitis from human coccidioidomycosis cases, while all eight primary samples from two animals (rhesus monkey and rhinoceros) were confirmed as C. posadasii. A preliminary analysis of cerebrospinal fluid (CSF) and pleural fluid samples showed positive correlation between serology tests and real-time PCR for two of the 15 samples. The Coccidioides spp. duplex real-time PCR will allow rapid differentiation of C. immitis and C. posadasii from clinical specimens and further augment the treatment and surveillance of coccidioidomycosis.